2003
DOI: 10.1007/s00122-003-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific SCAR markers in the dioecious plant Rumex nivalis (Polygonaceae) and implications for the evolution of sex chromosomes

Abstract: We developed SCAR primers based on isolated and sequenced male-specific fragments as identified in an AFLP analysis of the dioecious plant Rumex nivalis. PCR amplification using these primers on females and males resulted in fragments exclusively present in males. Coamplification of the nuclear rDNA internal transcribed spacer 2 together with the male-specific fragment was applied as an internal control for successful PCR reactions to avoid false-negative sex scoring. With a length of about 164 bp, the AFLP fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…To determine whether seeds and vegetative individuals sampled from the field and in the glasshouse experiment (described below) were female or male, we used male-specific sequence-characterized amplified-regions (SCAR) primers following the methods detailed in Stehlik and Blattner (2004). To avoid false negative scoring of sex, we co-amplified the nuclear rDNA internal transcribed spacer 2 (ITS2) together with the male-specific fragment as an internal control for successful PCR reactions.…”
Section: Dna Isolation and Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether seeds and vegetative individuals sampled from the field and in the glasshouse experiment (described below) were female or male, we used male-specific sequence-characterized amplified-regions (SCAR) primers following the methods detailed in Stehlik and Blattner (2004). To avoid false negative scoring of sex, we co-amplified the nuclear rDNA internal transcribed spacer 2 (ITS2) together with the male-specific fragment as an internal control for successful PCR reactions.…”
Section: Dna Isolation and Pcrmentioning
confidence: 99%
“…To avoid false negative scoring of sex, we co-amplified the nuclear rDNA internal transcribed spacer 2 (ITS2) together with the male-specific fragment as an internal control for successful PCR reactions. We subjected genomic DNA amounts of 3 ng to PCR in 12.5 l reaction volumes with 1.25 l 10ϫ PCR reaction buffer, 3 l of 10 mM MgCl 2 , 1 l of 10 mM dNTPs, 0.1 l of 25 pM of RnivYf and RnivYr (SCAR primers; Stehlik and Blattner 2004), 0.1 l of 5 pM ITS-B and ITS-D (Blattner 1999), 0.05 l 100ϫ BSA and 0.1 l 5 U/l Taq, adjusted with ddH 2 O. Cycling conditions were: 4 min at 94ЊC followed by 35 cycles of 45 sec at 92ЊC, 45 sec at 48ЊC, and 30 sec at 72ЊC and a final extension time of 10 min at 72ЊC. We visualized PCR products on 1.6% agarose gels stained with ethidium bromide.…”
Section: Dna Isolation and Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained this way can be questioned, however, because of the lack of information about the sex of ungerminated seeds. Information on Y chromosome-specific DNA sequences in Rumex (Shibata et al 1999;Stehlik and Blattner 2004) has been used to develop more convenient PCR-based methods of sexing sorrel seeds. Korpelainen (2002) showed that the primary sex ratio in Finnish populations of R. acetosa did not significantly differ from 1:1, and Stehlik and Barrett (2005) and Stehlik et al (2008) revealed a small but evident female bias in seeds of alpine R. nivalis from Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Korpelainen (2002) showed that the primary sex ratio in Finnish populations of R. acetosa did not significantly differ from 1:1, and Stehlik and Barrett (2005) and Stehlik et al (2008) revealed a small but evident female bias in seeds of alpine R. nivalis from Switzerland. The observed dissimilarity may conceivably be due to genetic differences between these plants: analysis of Y chromosome-specific sequences in R. nivalis showed a relatively large genetic difference between it and R. acetosa (Stehlik and Blattner 2004).…”
Section: Introductionmentioning
confidence: 99%